1991
DOI: 10.1139/o91-092
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of neutrophil elastase with hydrophobic polyanionic chelators

Abstract: The polyanionic calcium chelators, ethylenediamine-tetraacetic acid (EDTA), ethylene-bis-(oxyethylenenitrilo)-tetraacetic acid (EGTA), [bis-(O-aminophenoxy)-ethane-N,N,N',N'-tetraacetic acid (BAPTA), 1-[2-amino-5-(6-carboxyindol-2-yl) phenoxyl]-2-(2'-amino-5'-methylphenoxy)ethane-N,N,N1, N1-tetraacetic acid (INDO-1), 1-[2-(5-carboxyoxazol-2yl)-6-phenoxyl]-2-(2'-amino-5'- methylphenoxy)ethane-N,N,N',N'-tetraacetic acid (FURA-2), and 2-([2-bis-(carboxymethyl)-amino-5-methylphenoxy]-methyl(-6-methyl-8- bis-(bis-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…We have shown here that the serine proteases PMSF and AEBSF and the neutrophil‐specific elastase II inhibitor inhibited the cleavage of mCRP, strongly suggesting that the enzyme responsible is elastase. EDTA also prevented the degradation of mCRP by neutrophil‐derived enzymes, which is consistent with the observation that elastase requires calcium to function 33 . Shepard et al .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We have shown here that the serine proteases PMSF and AEBSF and the neutrophil‐specific elastase II inhibitor inhibited the cleavage of mCRP, strongly suggesting that the enzyme responsible is elastase. EDTA also prevented the degradation of mCRP by neutrophil‐derived enzymes, which is consistent with the observation that elastase requires calcium to function 33 . Shepard et al .…”
Section: Discussionsupporting
confidence: 84%
“…EDTA also prevented the degradation of mCRP by neutrophil-derived enzymes, which is consistent with the observation that elastase requires calcium to function. 33 Shepard et al showed that neutrophil-derived enzymatic cleavage of CRP resulted in fragments with biological activities; however, commonly a 30-fold molar excess over nCRP was required to induce cell activation. 34,35 Considering that only mCRP is susceptible to enzymatic degradation, it is questionable if in vivo sufficient levels of peptides could be generated to have any biological effect.…”
Section: Discussionmentioning
confidence: 99%
“…Other non-specific inhibitors of HLE are fatty acids, bile acids, and pyrene trisulfonic acid (Table IV) [121][122][123][124]. These compounds are all reversible inhibitors, and form no covalent interactions with the enzyme.…”
Section: Inhibitors Of Leucocyte Proteasesmentioning
confidence: 99%
“…HLE inactivation through active site acylation has been accomplished by β-lactams, isoxazolines, saccharins, and benzisothiazolones . Also reported as inhibitors of HLE are the chemical classes of phenylbutyrates, oligonucleotides, polyanionic chelators, heparin derivatives, peptidyl carbamates, sulfonamidobenzoylglycines, isocoumarins, and biphenyldisulfonic acid copolymer …”
Section: Introductionmentioning
confidence: 99%